First Detection and Molecular Analysis of Leishmania infantum DNA in Sand Flies of Kosovo - Xhekaj, Betim; Hoxha, Ina; Platzgummer, Katharina; Kniha, Edwin; Walochnik, Julia; Sherifi, Kurtesh; Rexhepi, Agim; Behluli, Behlul; Dvořák, Vit; Fuehrer, Hans-Peter; Obwaller, Adelheid G; Poeppl, Wolfgang; et al. (Pathogens (Basel, Switzerland), 2023)
Phlebotomine sand flies (Diptera: Psychodidae) are the principal vectors of phleboviruses and Leishmania spp., the causative agents of leishmaniases. The Mediterranean sand fly fauna is diverse, and leishmaniasis, mainly caused by Leishmania infantum, is endemic in the Balkan countries. Despite recent entomological surveys, only some districts of Kosovo have been sampled for sand flies, with no proof/confirmation of L. infantum. This study aimed to gain further insights into the species composition of natural sand fly populations in previously unsampled districts and areas in Kosovo without reports of leishmaniasis and to detect Leishmania DNA in sand flies. A sand fly survey was conducted in 2022 in all seven districts of Kosovo. Collected females were screened for Leishmania DNA by PCR. Positive samples were sequenced and subjected to maximum likelihood analysis with reference sequences for further molecular characterization. The trapping activities at 114 different localities resulted in 3272 caught specimens, comprising seven sand fly species of two genera, namely Phlebotomus neglectus, Ph. perfiliewi, Ph. tobbi, Ph. papatasi, Ph. simici, Ph. balcanicus and Sergentomyia minuta. Leishmania infantum DNA was detected in three individual sand flies of Ph. neglectus and Ph. perfiliewi. This study provides the most extensive sand fly survey in Kosovo and reports the first record of L. infantum DNA in sand flies, indicating autochthonous circulation of L. infantum.
Keywords: Balkan; Larroussius; leishmaniasis; Kosovo; PCR; Phlebotominae